Hazrat data gunj baksh(a.s) - Dr. Abdul Rauf (Ferozsons; Pakistan, 2005)
"Data Gunj Bakhsh (Ali Hujwiri, R.A.) was a revered Persian Sufi saint and scholar, known for his influential work Kashf al-Mahjub and spiritual teachings."